DISPARITAS PEMBANGUNAN MANUSIA DI SUMATERA UTARA - BANGUN, RITA HERAWATY (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The Human Development Index (HDI) is one indicator used to measure the achievement of the quality of life for human development. The achievements of human development in North Sumatra in 2019 are in the high category but inequality between regions is still found. Improving HDI achievements among regions in North Sumatra needs to be done as an implementation of sustainable human development goals by taking into account the supporting factors. The purpose of this study is to analyze and identify the factors that influence human development inequality in North Sumatra Province. This study is based on secondary data using cross-border data consisting of data on the percentage of poor population, open unemployment rates of economic growth by district and city in 2019. This study uses multiple linear regression analysis techniques. The results of the study prove that the variable percentage of poor population, open unemployment rate, and economic growth together influence inequality in human development. Partially the percentage of poor population and the level of open unemployment affect the inequality of human development while the variable of economic growth does not significantly influence.